Assessing the relative efficacy of interleukin-17 and interleukin-23 targeted treatments for moderate-to-severe plaque psoriasis: A systematic review and network meta-analysis of PASI response. - Laura M Sawyer; Kinga Malottki; Celia Sabry-Grant; Najeeda Yasmeen; Emily Wright; Anne Sohrt; Emma Borg; Richard B Warren (PLoS ONE)
Introduction New generation biologics, including interleukin (IL)-17 and IL-23 inhibitors, have delivered higher rates of skin clearance than older treatments in head-to-head studies. However, studies comparing these new biologics directly to one another are limited. Objectives To compare the short-term efficacy of available (or imminently available) biologic and non-biologic systemic therapies for treating patients with moderate-to-severe plaque psoriasis. Methods A systematic review was undertaken to identify randomised controlled trials evaluating biologic treatments, apremilast and dimethyl fumarate. MEDLINE, MEDLINE In-Process, Embase and the Cochrane Library were searched from the 1st January 2000 to 22nd November 2018. A Bayesian network meta-analysis (NMA) using a random-effects multinomial likelihood model with probit link and meta-regression to adjust for cross-trial variation in placebo responses compared the efficacy of interventions at inducing different levels of Psoriasis Area and Severity Index (PASI) response during the induction period. A range of sensitivity analyses was undertaken. Results Seventy-seven trials (34,816 patients) were included in the NMA. The base-case analysis showed that all active treatments were superior to placebo. IL-17 inhibitors, guselkumab and risankizumab were found to be more efficacious than tildrakizumab, ustekinumab, all TNF inhibitors and non-biologic systemic treatments at inducing all levels of PASI response. In addition, brodalumab, ixekizumab and risankizumab were significantly more efficacious than secukinumab; no significant difference was found in the comparison with guselkumab. The greatest benefit of brodalumab, ixekizumab, guselkumab, and risankizumab was seen for PASI 90 and PASI 100 response. Results were consistent across all analyses. Conclusions In the NMA brodalumab, ixekizumab, risankizumab and guselkumab showed the highest levels of short-term efficacy. There were differences in efficacy between treatments within the same class. Longer-term analyses are needed to understand differences between these drugs beyond induction in what is a life-long condition.